A indexação automática no processo de recuperação da informação: técnicas de análise de assunto operadas pelos softwares de indexação SISA, MHTX e o buscador Google - SILVA, Patrícia Teixeira da (2018)
The research presents the theme in the context of documentary languages, in which the problem identified for the development of this is to discover how the subject analysis is developed by indexing software: SISA, MHTX and the Google search engine. It presents as general objective in discovering different proposals of the accomplishment of analysis of subject in the automatic indexation; with specific objectives: a) present the historical survey of automatic and manual indexing; b) identify different forms of Consistency of automatic indexing; c) demonstrate the criteria and instruments used for representation in the software SISA, MHTX and the Google search engine. For the methodological development, the deductive method was used and the character is exploratory and a bibliographic survey is used to analyze the data. In the analysis of the data, different forms for application of the criteria and instruments for analysis of the subject to the automatic indexing between the software SISA (Semi-Automatic Indexing System) and MHTX and the Google search engine are verified. In this way, it is concluded that the use of terminological control provides better indexing both manually and automatically, such controls occur through thesauri, controlled vocabularies and ontologies. Thus the alliance between scholars from different areas of knowledge engaged in this purpose, will provide a recovery of information efficiently and effectively.